Tsunami Response in Batu Bengkung Beach Tourism, Gajahrejo Village, Malang Regency - Faisal Kurniawan Arifyanda; Darmansjah Tjahja Prakasa; Febby Rahmatullah Masruchin (Asian Journal of Social and Humanities, 2024)
Batu Bengkung Beach in Malang Regency has excellent potential as a natural tourist destination. However, the natural condition which is an area prone to tsunami disasters also cannot be ignored. Safety considerations and minimizing casualties are the main reasons this tour aims to make adjustments to aspects of tsunami disaster mitigation. Likewise for the sustainability of tourism in the future. The method carried out is through qualitative and quantitative data research. Direct observation at the location is also needed to determine exactly the existing conditions, as well as interviews with several resource persons as data reinforcement. The result is the application of aspects of tsunami disaster mitigation that are relevant to existing natural conditions. Aspects of tsunami disaster mitigation that can be applied are, first, the determination or determination of evacuation locations and evacuation routes. By utilizing natural conditions surrounded by hills, these conditions can be an ideal evacuation location. The second early warning is in the form of an alarm or siren warning of a tsunami. Aims to notify of the tsunami disaster and is expected to evacuate immediately. The third erected vertical evacuation buildings in the form of tsunami shelters that met FEMA guideline standards. And finally regular disaster mitigation simulation training.